PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE GUIDED NOTE TAKING (GNT) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII SMP NEGERI 34 PADANG - Armelia, Yuma; Rahmi, Rahmi; Lovia, Lita (Pendidikan Matematika, 2013)
This research is based by the understanding of mathematical concept that still low for some student. Student also lack of understanding every material that they noted. This research is also to find out how the development the understanding of student mathematical concept with applying the active learning strategy "guide note taking" type in the math learning of class VII student SMPN 34 padang and to know that the understanding of student mathematical concept with the applying the active learning Guided Note Taking Â type is better than applyinh a conventional learning of class VII student SMPN 34 padang. Type of research is experiment research with random design research to subject the population of research is class VII student SMPN 23 padang periode 2012/2013. The sample taking technique did as random. Class chosen as experiment class and as control class, the research instrument is quiz and understanding of mathematical concept is test like essay with realibility test 0,88. Analytic technique data using test t one side with minitab help. Based on data analytic result, it found that both sample classes are distributted nornally and homogen. The result hypothesis test got from p-value same as 0,048, it means smaller than a = 0,05, so the research hypothesis accepted and we can get the conclusion that the understanding of student mathematical concept with active strategy Guided Taking Note type better than the convensional learning with 95% level trust.